Direct shear tests on unsaturated soils - Toh, Timothy Hong Ern (2015)
This project aims to study the shear strength of unsaturated soil by conducting constant water content direct shear tests on residual soils of Bukit Timah Granite in Singapore. The soil specimens were obtained through compaction at different water contents to achieve a set of specific dry densities. Compaction was performed with a fabricated compaction apparatus which allowed the specimens to undergo direct shear test without trimming. The compaction procedures were based on ASTM D698 (2012) and ASTM D1557 (2012). The specimens were assumed to be sheared under undrained constant water content condition. Results from the tests were used to obtain the specimen failure envelopes, relationships between shear stress and net normal stress; vertical displacement and horizontal shear displacement; friction angle and water content/dry unit weight; cohesion and water content/ dry unit weight; ratio of the shear strength to net normal stress, τ/σ, and water content/dry unit weight.